The role of respiratory epithelium in host defence against influenza virus infection - Laura Denney; Ling-Pei Ho (Biomedical Journal, 2018)
The respiratory epithelium is the major interface between the environment and the host. Sophisticated barrier, sensing, anti-microbial and immune regulatory mechanisms have evolved to help maintain homeostasis and to defend the lung against foreign substances and pathogens. During influenza virus infection, these specialised structural cells and populations of resident immune cells come together to mount the first response to the virus, one which would play a significant role in the immediate and long term outcome of the infection. In this review, we focus on the immune defence machinery of the respiratory epithelium and briefly explore how it repairs and regenerates after infection. Keywords: Influenza, Airway epithelium, Defence, Sensing, Injury and repair